UJI RANCANGAN JMF CAMPURAN AC-WC MENGGUNAKAN MARSHALL TEST DAN REFLUKS EXTRACTOR - Hamduwibawa, Rofi Budi; Manggala, Adhitya Surya; Nurillah, Arif Wahyu (Universitas Majalengka, 2023)
The level of asphalt is a significant factor to consider. The levels of asphalt used in paved mixtures serve asa basis for good performance production to a maximum life of road service. The study used tangible concrete mixed taral-the wearing course (latrines) that would be tested to reflux extractors in comparison with the Marshall's so that it would be known to match the levels of asphalt in the solution. Research USES materials from amps in jember county. Afterward, a mixed design takes into account the proportion of other ingredients. The next activity in which objects were developed was used by JMF (job mix formula), which would be tested at optimumnyam asphalt, by way of a Marshall test and testing through a reflux. Research shows that the Marshall test results have been found that at tar 4.5% - 7.0% vma value, stability, density, output for Marshall, and flow meets the specs. For the value of asphalt level effective only 4.5% of asphalt does not meet specs. Vfa only levels of asphalt 6.0% - 7.0% meet the specs. For a vim score only 7.0% of asphalt meets the specs. Testing for extraction level asphalt with external refluses, extracts obtained obtained multiple extractions with JMF tarips still meet the specification of +-0.3% tolerance based on 2018 general specs.